Financial Crisis Wealth Losses and Responses among Older Households in England*. (12th June 2013) - Banks, James; Crawford, Rowena; Crossley, Thomas F.; Emmerson, Carl
Abstract Prices of real and financial assets fell substantially in the UK during 2008–09. The fourth wave of the English Longitudinal Study of Ageing (ELSA) was in the field throughout this 'financial crisis'. We use these data, and earlier ELSA waves, to document the effect of the crisis on those aged 50 and over in England, importantly taking into account that a significant proportion of the wealth of these households is held in forms such as state pensions that will not be directly affected by movements in asset prices. We find that the median fall in wealth among individuals was 8 per cent of total household gross wealth with, on average, richer individuals having experienced a larger decline. We find some evidence that those who experienced greater wealth shocks were more likely to reduce their expected chance of leaving a large bequest and to reduce their spending on certain 'semi‐luxury' items such as clothing and food consumed out of the home.